Conversion of laparoscopic cholecystectomy to open surgical procedure due to complete fibrosis of the gallbladder - Su, Lowell S (BMJ Publishing Group, 2013)
We present a case of transmural fibrotic gallbladder in a patient with previously undiagnosed gallbladder disease and describe our surgical approach to treating this patient.